Homophones facilitate lexical development in a second language. (July 2020) - Liu, Jiang; Wiener, Seth
Abstract: This study examined how previously learned words affect the acquisition of new words in a second language (L2). Twenty L1 English adults in a second semester L2 Mandarin Chinese class performed a three-day word learning experiment involving 10 tonal monosyllabic minimal pairs (e.g., ku4 'warehouse' – ku1 'to cry'). Half of the words were homophonous with previously learned words, while the other half were not. Half of the words contained syllables with high token frequencies, while the other half contained syllables with low token frequencies. Daily training included self-paced sound-image associations presented via headphones and computer, followed by a 4-alternative-forced-choice word identification task. A naming task was included on Day 3. On Day 1, participants showed a facilitative homophone effect: new words that were homophonous with previously learned words were more accurately identified than those that were not homophonous. On Day 2 and 3, new words that were homophonous with previously learned words were recognized faster than those that were not homophonous. Syllable token frequency did not affect accuracy or response time; neither homophone status nor syllable token frequency affected naming accuracy. Thus, previously acquired phonological and lexical information can positively affect L2 lexical development.